Activation of GABAA Receptors in Colon Epithelium Exacerbates Acute Colitis - Ma, Xuelian; Sun, Qian; Sun, Xiaotong; Chen, Dawei; Wei, Chuanfei; Yu, Xin; Liu, Chuanyong; Li, Yanqing; Li, Jingxin (Frontiers in Immunology, 2018)
ABSTRACT Emerging evidence indicates that gamma-aminobutyric acid (GABA) has many beneficial effects such as ameliorating immune and inflammatory response. But, here we reported that activation of GABAA Rs aggravated dextran sodium sulfate (DSS)-induced colitis although the expression of pro-inflammatory cytokines was inhibited. In contrast, blocking of GABAA Rs markedly alleviated DSS-induced colitis. Notably, GABAA Rs and GAD 65/67 were significantly increased in colon mucosa of UC patients and the mouse model of colitis. Further studies showed that GABA treatment resulted in an increment of serum FITC-Dextran following its oral administration, a decrement of transepithelial electrical resistance and an increment of bacterial invasion, effects which were blocked by bicuculline. In addition, GABA inhibited the expression of tight junction proteins and mucin secretion in colitis colon. GABA also decreased the expression of ki-67 and increased cleaved-caspase 3 expression in intestinal epithelia. Our data indicate that the GABAA Rs activation within colon mucosa disrupts the intestinal barrier and increases the intestinal permeability which facilitates inflammatory reaction in colon. Meanwhile, the suppression effect of GABA on pro-inflammatory cytokines leads to insufficient bacteria elimination and further aggravated the bacteria invasion and inflammatory damage.